Battery longevity of a helix-fixation dual-chamber leadless pacemaker: results from the AVEIR DR i2i Study - Reddy, Vivek Y; Doshi, Rahul; Ip, James E; Defaye, Pascal; Exner, Derek V; Canby, Robert; Shoda, Morio; Bongiorni, Maria G; Hindricks, Gerhard; Neužil, Petr; Callahan, Thomas; Badie, Nima; et al. (Europace, 2025)
AIMS: A dual-chamber leadless pacemaker (LP) system that employs distinct atrial and ventricular LP devices (ALP, VLP) has been introduced to clinical practice. Proprietary, low-energy, implant-to-implant (i2i) communication at each beat enables the devices to maintain synchronous atrioventricular sensing and pacing. We evaluated device longevities and contributing factors, such as i2i communication. METHODS AND RESULTS: Patients meeting dual-chamber pacing indications received the dual-chamber LP system as part of a prospective, multi-centre, international clinical trial (Aveir DR i2i Study, NCT05252702). Programming and diagnostics were interrogated from all de novo, non-revised, dual-chamber programmed devices at 12 months post-implant. This analysis included 302 patients (65% male; age 70 ± 13 years; weight 80 ± 19 kg; intrinsic heart rate 55 ± 7 bpm; 58% sinus node dysfunction, 27% atrioventricular block). At 12 months, devices were programmed to dual-chamber pacing (DDD(R) or DDI(R)) at a median 60 bpm rate, median 1.25 V pulse amplitude in ALP and 1.5 V in VLP, median 0.4 ms pulse width, and median i2i signal setting level 5 out of 7. Median ALP and VLP remaining battery longevities at 12 months were 4.3 and 9.1 years, with median total ALP and VLP longevities of 5.3 and 9.9 years. Base rate, pulse amplitude, pacing percentage, event rate, impedance, and i2i setting level all exhibited significant correlations with ALP and VLP longevities (P < 0.001). Programming i2i setting levels below 7 produced the greatest longevity savings. CONCLUSION: The first dual-chamber LP demonstrated adequate projected battery longevity after 12 months of use. Patient-specific device programming considerations, unique to leadless devices, may extend longevity.
Keywords: kardiostimulátor; Battery longevity; Humans; Electric Power Supplies; lidé středního věku; Leadless pacemaker; Equipment Design; Female; Aged; Aveir; Heart Rate; Time Factors; výsledek terapie; Cardiac Pacing, Artificial; senioři; lidé; zdroje elektrické energie; časové faktory; ženské pohlaví; Dual-chamber; Male; srdeční frekvence; Middle Aged; srdeční arytmie; atrioventrikulární blokáda; Treatment Outcome; design vybavení; Aged, 80 and over; senioři nad 80 let; Arrhythmias, Cardiac; kardiostimulace umělá; mužské pohlaví; prospektivní studie; Pacemaker, Artificial; Atrioventricular Block; Prospective Studies